Shakespeare’s Richard III: An Anomalous Protagonist in an Unusual Play - Whissell, Cynthia (Advances in Social Sciences Research Journal, 2020)
Shakespeare’s Richard III is studied in terms of the positivity of language in Richard’s speeches (close to 8000 emotionally scored words). Positivity is evaluated with the Dictionary of Affect in Language (Whissell, 2009). A plot line modeled with a polynomial regression is sketched for the entire drama on the basis of positivity. The overall emotion of the play is positive, and essentially comic (in comparison to Shakespeare’s oeuvre) but the trajectory of the plot of Richard III is tragic. Richard appears as a psychopath in most of the play but becomes more neurotic and conscience-stricken towards the end. The two discussions where Richard is attempting to force a marriage (with Anne, with Queen Elizabeth’s daughter) are compared and differentiated.